Jane Austen : a brief life - Stafford, Fiona J. (Yale University Press, 2017)
Every devoted reader feels that, in some way, they know Jane Austen. But how can we make sense of her extraordinary achievements? At a time when most women received so little formal education and none could obtain a place at university, how did Austen come to write novels that have commanded the attention of some of the most brilliant minds ever since? Why were hers the books that Darwin knew by heart and Churchill read during the Blitz? In this graceful introduction to the author's life and works, Fiona Stafford offers a fresh and accessible perspective, discussing Austen's six astonishing novels in the context of their time. Newly updated, Jane Austen: A Brief Life offers a rich and sympathetic insight into a writer who was just as much the Romantic genius as Keats, Shelley or Byron - full of youthful exuberance, intensely creative once she had found her individual voice, and dead before she reached middle age.
Keywords: Austen, Jane, -- 1775-1817.; Austen, Jane, -- 1775-1817; Austen, Jane -- 1775-1817; Novelists, English -- 19th century -- Biography.; BIOGRAPHY & AUTOBIOGRAPHY -- Literary.; LITERARY CRITICISM -- European -- English, Irish, Scottish, Welsh.; Novelists, English; 1800-1899; Biographies